Educational Transformation through Visionary Leadership: A Study at State Madrasah Tsanawiyah 5 Cilacap - Suparyo, Suparyo; Hanif, Muh. (Asian Journal of Applied Education (AJAE), 2025)
Quality education is closely related to leaders. Leaders who have a vision, are creative, and innovative will be able to advance education in Indonesia. With the progress of education, the community will be satisfied with the needs needed. This study aims to determine the madrasah head's policy in achieving the vision, mission, and educational goals and to find visionary leadership in implementing the vision for the advancement of academic quality. To get good findings, researchers used a qualitative approach. Data collection was conducted using interviews, observation, and documentation. The research informants were the head of the madrasah, the deputy head of the madrasah, and several teachers. This study found that visionary leadership is implemented optimally. This can be seen as follows: 1) Formulating Vision. The formulation of this vision is based on the personal values of the madrasah head. The madrasah principal changed the vision of the madrasah to be more focused in the future by evaluating activities once a semester. Hold weekly meetings to listen to suggestions or complaints from teachers. The principal also makes short and long-term programs. That way the planned activities will run according to plan. 2) Implement the Vision. In implementing the vision, the madrasah principal does things such as giving birth to 5 madrasah principles 1) Faithful, 2) Order and discipline, 3) Ahlakul Karimah, 4) Ukhuwah Islamiyah, 5) Capable. In addition, in implementing